Characterization of a Compound Starch-Based Adsorbent for Alcohol—Water Azeotrope Dehydration - Jinsheng Sun; Wenping Wang; Pei Wang; Hao Lv; Xubo Luo; Hong Gao (Adsorption Science & Technology)
Biosorptive dehydration processes of ethanol, isopropanol and t-butyl alcohol (TBA) using a specially formulated compound starch-based adsorbent (CSA) were investigated and analyzed. The inverse gas chromatography (IGC) experimental results indicated that the CSA was effective for the selective separations at the alcohol and water azeotropes. using batch adsorption and regeneration experiments, the optimal adsorption and regeneration conditions were determined by single-factor and orthogonal design methods. A comparison of the results from the IGC and batch adsorption experiments of the three azeotrope systems suggested that the separation factors increased with decreasing alcohol polarities and increasing numbers of alcohol carbon atoms, which may be related to the transport properties and strength of the interactions between the alcohol and free OH groups on the glucose units in the CSA. The field emission scanning electron microscopic images and pore-size distributions indicated that the main component of the CSA macro-porous structure played a major role in adsorption. Cycling adsorption/regeneration experiments demonstrated the reusability of the CSA.